Area ratio effects to the performance of air-cooled ejector refrigeration cycle with R134a refrigerant - Jia, Yan (2013)
In this paper, the key ejector geometry parameters for an air-cooled ejector cycle using R134a with cooling capacity of 2 kW are designed by 1D analysis. Through enlarging the designed area ratios by connecting the replaceable nozzles with a main body, optimum area ratios under air-conditioning working conditions are studied experimentally. Three parameters, namely, the entrainment ratio, COP and cooling capacity are evaluated, and the results show that the optimum area ratios are from 3.69 to 4.76 that are lower than those mentioned in other studies. With a fixed area ratio, experiments also show that the influence of the ejector area ratio on the ejector performance largely depends on the operating conditions. Consequently, the effects of operating conditions such as primary flow pressures on the ejector system performance are evaluated.